PRAKTIK TABUNGAN MASYARAKAT PEDESAAN DALAM PERSPEKTIF FIKIH MUAMALAH - Ayuk Dian Rahmawati; Amirullah Amirullah; Fachrudin Fiqri Affandy (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2020)
This thesis aims to analyze Ngudi Tentrem's savings practices from the perspective of fiqh muamalah in 4th Neighborhood, 2nd Hamlet, Ongan Jaya Village, Yapsi District, Jayapura Regency. This research also discusses the management's efforts to resolve the bad credit problems experienced by Ngudi Tentrem's savings practice. This study is qualitative research using primary and secondary data. The data analysis technique used is the phenomenological paradigm approach. The results of this study indicate that Ngudi Tentrem's savings practices in Ongan Jaya Village are carried out under the pillars and conditions of al-wadi'ah yad adh-dhamanah which involve the contract of two people who have faith, the existence of goods entrusted, and also ijab and qabul. The effort is restructuring which the management will provide interest relief and extension of time to creditors to save trouble to fulfill his obligations. The other way to resolve the bad credit problem is to settle with deliberation peacefully. The phenomenon of the survival of Ongan Jaya village savings is the culture of mutual aid which is still very thick in rural areas. Sense of solidarity and trust make this savings can be borne from its inception in 1997 until now, even though it does not have an official legal entity. The absence of collateral in these savings also adds to the value of its uniqueness, so, the people of Ongan Jaya village, especially, 4th Neighborhood, 2nd Hamlet prefer to choose Ngudi Tenrem savings practice.